1997
DOI: 10.1029/96jd03782
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range transport of SOx and dust in East Asia during the PEM B Experiment

Abstract: Abstract. The transport of SO2 and surfate in East Asia (including eastern China, Korea, and Japan) during the period of March 1 through March 14, 1994, is studied using a three-dimensional regional-scale atmospheric chemistry model. This period corresponds to that in which the Pacific Exploratory Mission in the Western Pacific Ocean (PEM-West B) was being conducted around Japan. During this period, characterized by the passage of cold fronts and relatively dry conditions, the anthropogenic sulfur emitted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…However, the total sulfate inside the dust cloud increased by less than 2% because decreases in fine sulfate essentially compensated increases in coarse sulfate. Previous model studies have suggested that dust could increase the local sulfate mass burden by 10-100% downwind of E. Asia (Bauer and Koch, 2005;Dentener et al, 1996;Song and Carmichael, 2001;Xiao et al, 1997). These studies also predicted that up to 70% of sulfate was present at coarse sizes over the Yellow Sea and Sea of Japan, at dust concentrations over an order of magnitude lower than observed in ACE-Asia.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, the total sulfate inside the dust cloud increased by less than 2% because decreases in fine sulfate essentially compensated increases in coarse sulfate. Previous model studies have suggested that dust could increase the local sulfate mass burden by 10-100% downwind of E. Asia (Bauer and Koch, 2005;Dentener et al, 1996;Song and Carmichael, 2001;Xiao et al, 1997). These studies also predicted that up to 70% of sulfate was present at coarse sizes over the Yellow Sea and Sea of Japan, at dust concentrations over an order of magnitude lower than observed in ACE-Asia.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 10-30% of the sulfate mass was observed at super-micron sizes in flights 6, 7 and 8 of the ACE-Asia experiment. Most of the ACEAsia observations were made at dust concentrations of 100-1000 µg m −3 , which are a factor 10-100 greater than simulated by Dentener et al (1996), Xiao et al (1997) and Song and Carmichael (2001). These studies did not consider surface saturation effects when modeling heterogeneous reactions between SO 2 and dust, which allowed SO 2 to be continually oxidized to sulfate on the dust surface.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations